Hot compression deformation behaviour and microstructure evolution of Ti-3.5Al-3.5V-0.5Fe-0.6Mo-0.5Cr alloy. (1st March 2023) - Zhu, Mingting; Liu, Rui; Song, Xiaoyun
Abstract: Ti-3.5Al-3.5V-0.5Fe-0.6Mo-0.5Cr alloy is a new superplastic titanium alloy The alloy was deformed by plane strain compression at 820°C 880°C, 0.16 s −1 8 s −1, which can provide reference for obtaining homogeneous microstructure during the rolling process. The results show that the flow stress of the alloy has a negative correlation with the deformation temperature and a positive correlation with the strain rate. The flow softening behavior of alloy is greatly influenced by deformation temperature. The fraction and the length of α lamellar increase with the decrease of temperature, and the flow-softening phenomenon of the alloy is more obvious. The homogeneity of microstructure and the recrystallization ratio of α lamellae increase with the increase of deformation temperature and the decrease of strain rate. The alloy can obtain homogeneous microstructure at 850°C, 0.16 s −1, and 880°C, 0.16 s −1 1.6 s −1 deformation conditions.